Learning Environment and Attitudes in Middle School Mathematics - Giles, Rhiannon Mignon (Curtin University, 2019)
With a sample of 221 year 9 students from South Australia, six aspects of classroom environment (student cohesiveness, teacher support, involvement, task orientation, cooperation and equity) were related to several aspects of students’ attitudes to mathematics. Two different methods of analysis identified moderate and positive associations between classroom environment and attitudes. In particular, classroom involvement and task orientation were linked with students enjoying mathematics more and having more-positive attitudes to mathematical inquiry.